Rancang Bangun Mini Game Pengenalan Senjata Tradisional (Kurambik, Ruduih, Karih) Menggunakan Teknologi VR Head Mounted Display - Danny Sevia Ningrum; Sheanny Ocmi Sakti (Lembaga Yasin AlSys, 2026)
Although the use of virtual reality for cultural preservation continues to develop, the development of immersive minigames specifically introducing kurambik, ruduih, and karih remains limited. This study aimed to develop a virtual reality-based minigame using a head-mounted display as an interactive and safe medium for introducing traditional Minangkabau weapons. The study employed a research and development approach using the Multimedia Development Life Cycle model, which comprised the concept, design, material collecting, assembly, testing, and distribution stages. Data were collected through observations at Museum Adityawarman Padang, documentation, a literature review, interviews, and functional testing. The data were analyzed using a qualitative descriptive approach by comparing the application outputs with the planned features. The results showed that the application successfully presented a Minangkabau-themed virtual environment, three-dimensional weapon models, information panels, grab and slice systems, scores, time limits, and three different minigames. Kurambik was used to cut fruit, ruduih to slash bamboo, and karih to confront ghost objects. The alpha testing results showed that all primary functions could be operated after optimizing the low-poly models, adjusting the colliders, and correcting the attach points. This study produced a prototype of an immersive experience-based cultural education medium that can support the interactive and safe introduction of traditional Minangkabau weapons. Future research should conduct beta testing, measure improvements in users’ knowledge, and involve cultural experts and users with more diverse characteristics.